CDCP1 expression is frequently increased in aggressive urothelial carcinoma and promotes urothelial tumor progression - Saponaro, Miriam; Flottmann, Sina; Eckstein, Markus; Hommerding, Oliver; Klümper, Niklas; Corvino, Dillon; Hosni, Sana; Schmidt, Anja; Mönig, Nicolas; Schmidt, Doris; Ellinger, Jörg; Toma, Marieta; et al. (Scientific Reports, 2023)
The prognosis of patients with advanced urothelial carcinoma (UC) remains poor and improving treatment continues to be a major medical need. CUB domain containing protein 1 (CDCP1) is a known oncogene in various types of solid cancers and its overexpression is associated with impaired prognosis. However, its role in UC remains undetermined. Here we assessed the clinical relevance of CDCP1 in two cohorts of UC at different stages of the disease. Immunohistochemistry showed that CDCP1 is highly expressed in advanced UC, which significantly correlates with shorter overall survival. Importantly, the basal/squamous UC subtype showed significantly enriched CDCP1 at the mRNA and protein levels. The functional role of CDCP1 overexpression was assessed taking advantage of ex vivo organoids derived from the CDCP1pcLSL/+ transgenic mouse model. Furthermore, CDCP1 knockout UC cell lines were generated using CRISPR/Cas9 technology. Interestingly, CDCP1 overexpression significantly induced the activation of MAPK/ERK pathways in ex vivo organoids and increased their proliferation. Similarly, CDCP1 knockout in UC cell lines reduced their proliferation and migration, concomitant with MAPK/ERK pathway activity reduction. Our results highlight the relevance of CDCP1 in advanced UC and demonstrate its oncogenic role, suggesting that targeting CDCP1 could be a rational therapeutic strategy for the treatment of advanced UC.
CRIS-Team Scopus Importer:2023-01-13